Peer Feedback Tool for Clinical Teaching - Elisa Zenni; Heather Hageman; Janet Hafler; Maryellen Gusic (Association of American Medical Colleges, 2011)
Abstract This resource is a peer feedback tool for clinical teaching, designed to provide assessment through peer observation of effective teaching behaviors. It aims to provide context and structure to peer observation and to help observers give meaningful feedback to teachers. Intended to promote formative feedback, a checklist format is utilized, complemented by space for open-ended comments. This tool can be used by individual faculty to enhance teaching, by institutions in faculty development efforts, and in processes to recognize and reward excellence in teaching. Feedback regarding the usefulness of the form has been uniformly positive. The teaching faculty found that the peer review process reinforces the effective aspects of their current teaching approaches, stimulates the development of teaching improvement behaviors, promotes self-reflection about teaching, and motivates them to explore other opportunities to enhance teaching. The reviewers found that their feedback skills were improved through the use of the checklist and that they learned new teaching behaviors through the observations.